The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1742-6596/1811/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties a Membrane of the Mixing PVA Nanocomposite and Limestone Hydroxyapatite

Abstract: Synthesis and characterization of membranes from a mixture of PVA nanocomposites and limestone hydroxyapatite have been carried out. The limestone is crushed, sieved with a size of 200 mesh. The synthesis of hydroxyapatite was carried out by heating limestone powder using a furnace at a temperature of 600 °C for 4 hours. Furthermore, limestone was dissolved with distilled water and 0.3M H3PO4 solution using a magnetic stirrer with stirring at 300 rpm for 1 hour. The pH of the solution was made 10 by adding 1 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These films hold immense promise as they combine natural components to create packaging materials that are not only eco-friendly but also possess enhanced functionalities (Yulianto et al, 2023;Bukit et al, 2023). With the global call for reducing plastic waste and environmental impact, these innovative bionanocomposite films represent a crucial step towards a greener and more sustainable future for the packaging industry (Wu et al,2019; Sirait et al, 2023). Sugar palm starch and chitosan, two biopolymers with abundant availability, have emerged as prominent components in the design of bionanocomposite packaging films (Nazrin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These films hold immense promise as they combine natural components to create packaging materials that are not only eco-friendly but also possess enhanced functionalities (Yulianto et al, 2023;Bukit et al, 2023). With the global call for reducing plastic waste and environmental impact, these innovative bionanocomposite films represent a crucial step towards a greener and more sustainable future for the packaging industry (Wu et al,2019; Sirait et al, 2023). Sugar palm starch and chitosan, two biopolymers with abundant availability, have emerged as prominent components in the design of bionanocomposite packaging films (Nazrin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in research [9] which concluded that nanocellulose can be added to the manufacture of PVA composites because it can increase mechanical characteristics such as tensile strength and elongation percentage. Synthesized limestone mixed with polyvinyl alcohol to obtain a nano-composite membrane that has good mechanical properties at a 1% mixture with Young's modulus of 22.28 M.Pa and a tensile strength of 13.23 M.Pa [10]. In this research, rice husks will be used as a filler to produce nanocomposites which can be used as automotive materials.…”
Section: Introductionmentioning
confidence: 99%